Barrier or breach? Assessing swine housing features for mosquito threats - Hanthorn, Christy J.; Cohnstaedt, Lee W.; Cernicchiaro, Natalia (Frontiers in Insect Science, 2025)
Effective mosquito control is critical in swine production to reduce disease transmission and prevent mechanical damage. However, current biosecurity measures on swine premises primarily target microbial pathogens, often overlooking the importance of excluding insects, particularly mosquitoes. While vector-borne disease transmission is the primary concern, mosquito infestations also contribute to mechanical damage, leading to secondary infections, stress-related production losses, and compromised animal welfare. Mitigation efforts aimed at mosquitoes can also have broader benefits by reducing other insect pests that compromise swine health. Despite the availability of tools and strategies for mosquito monitoring and control, standardized protocols and evaluations of effectiveness remain limited. This study aims to assess the protective attributes of swine housing against mosquito threats and identify vulnerabilities that may increase the risk of insect-borne diseases. By understanding these factors, targeted biosecurity strategies can be developed to enhance insect exclusion and reduce the overall impact of mosquito infestations on swine health and production. A key focus of this assessment is the reduction of mosquito populations within and around swine housing facilities. By providing swine producers and veterinarians with actionable insights and practical mitigation strategies, this study seeks to strengthen mosquito management efforts, ultimately improving herd health, productivity, and overall biosecurity.